FIGURATIVE LANGUAGE AND CONTEXTUAL MEANING: IN THOMAS HARDY POEMS - Septa Aryanika; Ayu Anggraini; Nunun Indrasari (Wiralodra English Journal, 2022)
Despite the growing body of research documented the analysis of poem in EFL learning, relatively few of literature examines the representation of figurative language and textual meaning situated in the ELT context. To fill this gap, the objective of figurative language is to enhance a poem's beauty and unique effects by also creating it much more interesting and distinctive. This research goal is to examine the representation of figurative language and contextual meaning in Hardy poems. The poems scrutinized by the researcher were "Ah Are You Digging On My Grave," "The Man He Killed," and "Neutral Tones."  Grounded in qualitative research with the content analysis design, this study portraited the representation of figurative language and contextual meaning in the poem as the EFL learning material. Drawing on the findings revealed that there are ten figurative language types in those poems, they are personification (21.43%), hyperbole (14.29%), synecdoche (14.29%), simile (14.29%), irony (11.90%), metaphor (7.14%), symbol (7.14%), allusion (4.76%), paradox (2.38%), and apostrophe (2.38%). There are 42 expressions in those poems. This study contributes the benefits to the EFL teachers and students as a reference of literature and semantics material in EFL learning.